Comparative pharmacokinetics of tacrolimus in stable pediatric allograft recipients converted from immediate‐release tacrolimus to prolonged‐release tacrolimus formulation. (1st April 2019) - Rubik, Jacek; Debray, Dominique; Iserin, Franck; Vondrak, Karel; Sellier‐Leclerc, Anne‐Laure; Kelly, Deirdre; Czubkowski, Piotr; Webb, Nicholas J. A.; Riva, Silvia; D'Antiga, Lorenzo; Marks, Stephen D.; Rivet, Christine; et al.
Abstract: This study was a Phase II, open‐label, multicenter, single‐arm, cross‐over study comparing the pharmacokinetics (PK) of tacrolimus in stable pediatric kidney, liver, or heart allograft recipients converted from immediate‐release tacrolimus (IR‐T) to prolonged‐release tacrolimus (PR‐T). In Days −30 to −1 of screening period, patients received their IR‐T‐based regimen; during Days 1‐7, patients received study IR‐T (same dose as screening). On Day 7, the first 24‐hours PK profile was taken; patients were then converted to PR‐T (1 mg:1 mg), with a second 24‐hours PK profile taken on Day 14. The primary end‐point was tacrolimus area under the blood concentration–time curve over 24 hours (AUC24 ); secondary end‐points were maximum concentration C max and concentration at 24 hours C24 . The predefined similarity interval for confidence intervals (CIs) of least squares mean (LSM) ratios was 80%‐125%. The PK analysis set comprised 74 pediatric transplant recipients (kidney, n = 45; liver, n = 28; heart, n = 1). PR‐T:IR‐T LSM ratio (90% CI) was similar overall for AUC24, max, and C24, and for kidney and liver recipients for AUC24 (LSM ratio, kidney 91.8%; liver 104.1%) and C24 (kidney 90.5%; liver 89.9%). Linear relationship was similar between AUC24 and C24, and between PR‐T and IR‐T (rho 0.89 and 0.84, respectively), suggesting that stable pediatric transplant recipients can be converted from IR‐T to PR‐T at the same total daily dose, using the same therapeutic drug monitoring method.